Determinants of foreign direct investment flows in Malaysia / Muhammad Syamsul Kamal and Abdul Rahim Mohd Yusof - Syamsul Kamal, Muhammad; Mohd Yusof, Abdul Rahim (Faculty of Business and Management, 2015)
This paper aims at examining the significant relationship between Malaysian FDI and macroeconomic variables. This study will focus on the Malaysian FDI value that will affected by macroeconomic variables. The sample of this research comprises of macroeconomic variables for 30 years. Methodology used for this study is by using Multiple Linear Regression Analysis. The sample selected using DataStream, World Bank database and journal. The dependent variable will be the Malaysian FDI, while the independent variables are Exchange rate, Inflation rate, Export goods & services, economic growth and China's FDI. The results of this research paper would provide us with an indicative view and could form an important basis for investors and policy makers in their investment strategies and policy decisions respectively.